2018
DOI: 10.1016/j.micpro.2018.07.008
|View full text |Cite
|
Sign up to set email alerts
|

Continuous face authentication scheme for mobile devices with tracking and liveness detection

Abstract: We present a novel scheme for continuous face authentication using mobile device cameras that addresses the issue of spoof attacks and attack windows in state-of-the-art approaches. Our scheme authenticates a user based on extracted facial features. However, unlike other schemes that periodically re-authenticate a user, our scheme tracks the authenticated face and only attempts re-authentication when the authenticated face is lost. This allows our scheme to eliminate attack windows that exist in schemes authen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 32 publications
(45 reference statements)
0
10
0
Order By: Relevance
“…The SVM-HMM model provides the best result when compared with naïve Bayes and cosine similarity. In [22], the author trained SVM classifier on facial attributes extracted from real images to build a continuous classification scheme. Results indicated that the proposed scheme shows a significant improvement on the existing continuous facial recognition system.…”
Section: Astesj Issn: 2415-6698mentioning
confidence: 99%
“…The SVM-HMM model provides the best result when compared with naïve Bayes and cosine similarity. In [22], the author trained SVM classifier on facial attributes extracted from real images to build a continuous classification scheme. Results indicated that the proposed scheme shows a significant improvement on the existing continuous facial recognition system.…”
Section: Astesj Issn: 2415-6698mentioning
confidence: 99%
“…Correct classification can be achieved by using classifiers, such as SVM (Support Vector Machine), DT (Decision Tree), and K-NN (k nearest neighbors). Online authentication is also possible in combination with physiological biometric authentication [12]. For example, the characteristic features of the face obtained with a smartphone camera can be used as a source of reference data.…”
Section: Related Workmentioning
confidence: 99%
“…Several of the thus far presented authentication schemes [7], [9], [10], [12] designed for the mobile environment focus on a single authentication factor. Thus, these protocols are not in line with the strong authentication objectives of EU Regulations [1] and NIST requirements [2] [3].…”
Section: Related Workmentioning
confidence: 99%
“…As the masking module performs masking on objects that have been recognized by the object identification module, the access permission DB module holds authentication information that discerns the status of the access permission granted to the user on each object (allowed vs. denied) and offers authentication information regarding each object upon requests from the masking module. Depending on the level of access rights stored in the access permission DB module, requesters of visual information may obtain different results from the same visual information due to the difference in the scope of masking provided [62][63][64][65].…”
Section: Access Permission Db Modulementioning
confidence: 99%
“…visual information may obtain different results from the same visual information due to the difference in the scope of masking provided [62][63][64][65].…”
Section: Comparisons Amongst Privacy Masking Techniques and Devicesmentioning
confidence: 99%